The Use of 81mKr Gas for the Measurement of Absolute Regional Lung Ventilation - Nosil, J.; Bajzer, Ž.; Spaventi, Š. (Nuklearmedizin - NuclearMedicine, 1977)
In this paper a new method of using 81mKr for the measurement of specific absolute regional lung ventilation is described. Experimental data suitable for the calculation of quantitative regional ventilation are provided using an adequate respiratory system for 81mKr dosage and a scintillation gamma camera interfaced to a digital computer.A simple mathematical lung model for the inhalation of 81mKr is used to determine the specific ventilation and the parameters proportional to the ventilation for the whole lung and different lung regions in patients and in healthy subjects.The lung count rate for a given region correlated well with the ventilation of that region. Clinical examples are given and discussed.